Sound characteristics for swiftlets attraction - Siti Nurzalikha Zaini , Husni Zaini (2012)
This project research about the analysis of sound can attract the swiftlets enter in swiftiets house. This is because the main swiftiets character is attraction toward sound. But the problem is doing not have any research to identify sound characteristic most are swiftiets more attract. These are important use for industry to attract swiftiets enter and build their nests in man-made house. In house fitted bird-call recording in cave to attract attention bird go inside house to be doing nest. Therefore, this study shall be analyzing sound features that there is in bird-call recording that has attracted attention bird. The methpd that will be used is taking a few of sample of swiftiets sound for analysis by using Matlab software. From analysis can identify sound characteristic where can attrct swiftiets from analysis the signal. The expectation from this research is can find sound characteristic for swiftlets attraction by analysis the frequency and amplitude of noise sound and original sound.